高コレステロール血症の治療方法 (2023)
対象における、上昇した血漿コレステロール値を低下させる方法を開示する。対象における高コレステロール血症の治療方法もまた開示する。方法は、コレステロール低下薬剤の不在下で対象に、有効量の化合物１：JPEG2023538066000007.jpg35127またはその薬学的に許容される塩を投与することを含む。 Disclosed is a method of lowering elevated cholesterol plasma levels in a subject. Also disclosed is a method of treating hypercholesterolemia in a subject. The methods comprise administering to the subject in the absence of a cholesterol lowering drug an effective amount of Compound 1 or pharmaceutically acceptable salt thereof.